An intellectual component recognition for security subsystem - Drach, T. A.; Goloskokov, A. E. (NTU "KhPI", 2017)
Discovered and proved the overall structure of the algorithms used in pattern recognition. A comparative analysis of methods and approaches to solving the problem of finding and identifying human face on the image. A modified algorithm for image scaling and clustering, which reduces the number of informative tracts candidates for the location of the research object (human face) is proposed. It is established that the use of neural networks coagulation makes a small number of errors in a large number of coagulation and other layers. It is established that the network has a large invariance to position the face in the picture. In consequence of that generalization ability higher than the multilayer perceptron. Evaluating the effectiveness of probabilistic systems showed that the use of the proposed approaches and algorithms enables a high probability likely face recognition (93%). Results of the study can be used in the development of automated systems for access: a personal computer, a bank account, application to access data on the image of a human face in miniature devices where there is no possibility to embed common hardware identification.

Виявлено та обґрунтовано загальну структуру алгоритмів, які застосовуються у сфері розпізнавання. На основі проведеного дослідження пропонується створити математичне та алгоритмічне забезпечення задачі розпізнавання образів, яке буде забезпечувати швидкодію та високу ймовірність розпізнавань. Проведено порівняльний аналіз методі та підходів до вирішення задачі знаходження та ідентифікацію обличчя людини на зображенні. Запропоновано модифікований алгоритм масштабування та кластеризації зображення.
Інтелектуальна компонента розпізнавання образів у підсистемах безпеки
Keywords: recognition system; optimization; machine learning; image; information criterion; functional efficiency; розпізнавання обличь; кластеризації; ідентифікація; інформативні ознаки; згортальна нейронна мережа